A Role for PPARγ in the Regulation of Cytokines in Immune Cells and Cancer - Xiao Yi Yang; Li Hua Wang; William L. Farrar (PPAR Research)
Peroxisome proliferator-activated receptor γ (PPARγ) is a ligand-activated transcription factor and a member of the nuclear receptor superfamily. PPARγ and its ligands appear to serve diverse biological functions. In addition to the well-studied effects of PPARγ on metabolism and cellular differentiation, abundant evidence suggests that PPARγ is an important regulator of the immune system and cancers. Since cytokines are not only key modulators of inflammation with pro- and anti-inflammatory functions but they also can either stimulate or inhibit tumor growth and progression, this review summarizes the role for PPARγ in the regulation of cytokine production and cytokine-mediated signal transduction pathways in immune cells and cancer.